The recruit : a novel - Drew, Alan, 1970- (Random House, 2022)
"Santa Elena in 1985 is a sleepy, sedate town-that is, until unusual crimes start to occur. The body of a dog is left outside a Vietnamese grocery store. An encampment of Mexican strawberry pickers is brutally attacked with mysterious weapons. A wealthy real estate developer is found dead inside the pool of his beach-side house. When rat poison and other clues are found across these crime scenes, Detective Ben Wade and forensic expert Natasha Betencourt begin to wonder: Are these crimes connected? As Ben and Natasha uncover a string of heightening racist incidents, they begin to suspect a gang of young people is part of the town's vicious underbelly, and part of a much larger nationwide racist conspiracy. This gripping new novel captures the lethal cost of deep-seated ignorance, racism, and hateful violence"--